Pengaruh Online Customer Review, Free Shipping dan Discount Terhadap Purchase Decision Generasi Z pada Marketplace Shopee di Daerah Istimewa Yogyakarta - Arya Dimas Nugraha; Awan Santosa (Universitas Mercu Buana Yogyakarta, 2025)
This study aims to analyze the influence of online customer review, free shipping, and discount on the purchase decision of Generation Z on the Shopee marketplace in the Special Region of Yogyakarta. The research method used is explanatory quantitative, with data collected through online questionnaires from 100 respondents. The analysis used in this study is descriptive analysis, multiple regression analysis, coefficient of determination, and partial t-test. Multiple linear regression analysis results indicate that online customer review and discount have a positive and significant effect on purchase decision, while free shipping does not show a significant influence. These findings provide practical implications for businesses to optimize marketing strategies based on reviews and discounts, as well as to evaluate the effectiveness of free shipping programs. This study also opens opportunities for further research by expanding variables and respondent coverage.